Effects of outdoor physical training on VO₂max, endurance, and power in male Sports Science students - Glady Sukma Perdana; Ilham Ilham; Ary Suud Cahyo Alben; Bekir Erhan Orhan; Vlad Adrian Geantă (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Background: Physical fitness is a key component of overall health, particularly for students in physical education programs. Outdoor-based physical training has been explored to enhance specific fitness components, including VO2max, muscle endurance, and leg explosive power. However, evidence on its effectiveness remains limited, particularly in areas such as leg power. Purpose: This study aimed to evaluate the effects of an 8-week outdoor-based physical training program on VO2max, arm muscle endurance, abdominal endurance, and leg muscle power in first-year male students. Materials and Methods: A pre-experimental, one-group pretest-posttest design was employed. Thirty-three first-year students from the Physical Education, Health, and Recreation program at Bung Hatta University were selected using purposive sampling. Physical fitness was assessed before and after the intervention. The following tests were used: VO2max via the bleep test, arm endurance with the 1-minute push-up test, abdominal endurance with the 1-minute sit-up test, and leg power with the standing broad jump test. Data were analyzed using paired t-tests, conducted with Microsoft Excel and SPSS version 25.  Results: Significant improvements were observed in VO2max (t = -9.077, p < 0.001), arm endurance (t = -8.433, p < .001), and abdominal endurance (t = -6.571, p < 0.001). However, no significant change was found in leg muscle power (t = 0.924, p = 0.362).  Conclusion: Outdoor-based physical training effectively enhances VO2max and muscle endurance. However, it may require a longer duration or increased intensity to improve leg explosive power. This differentiates the program from conventional indoor training methods by emphasizing adaptability and engagement in outdoor settings. Further adjustments to the training program are recommended to optimize overall physical fitness improvements.